IMPACT OF PANDEMIC COVID-19 ON CONSUMER PURCHASE INTENTION: EMPIRICAL STUDY FROM INDONESIA - Sakapurnama, Eko; Safitri, Nurul (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
The Covid-19 pandemic has caused an economic recession in many countries around the world. The economy has contracted with reduced customer demand due to the policy of large-scale social applications in Indonesia. This study aims to analyze consumer preferences from the demand-side side of several industrial sectors affected by the pandemic so that business players can develop strategies during the pandemic and post-Covid-19. The research was carried out on September 14-30, 2020, through an online survey of 722 respondents who live in the Jakarta, Bogor, Depok, Tangerang, and Bekasi areas. The results showed that in addition to basic needs, which occupy the first preference, consumers prefer to withhold their consumption of other commodity goods. According to the study findings, the transportation and tourism industry sectors are the weakest. The vehicle purchase subsector during the pandemic is also the lowest. Therefore, innovative policies are needed for businessmen or government policies to stimulate the automotive industry.